Propolis: A Detailed Insight of Its Anticancer Molecular Mechanisms - Suhib Altabbal; Khawla Athamnah; Aaesha Rahma; Adil Farooq Wali; Ali H. Eid; Rabah Iratni; Yusra Al Dhaheri (Pharmaceuticals, 2023)
Cancer is the second most life-threatening disease and has become a global health and economic problem worldwide. Due to the multifactorial nature of cancer, its pathophysiology is not completely understood so far, which makes it hard to treat. The current therapeutic strategies for cancer lack the efficacy due to the emergence of drug resistance and the toxic side effects associated with the treatment. Therefore, the search for more efficient and less toxic cancer treatment strategies is still at the forefront of current research. Propolis is a mixture of resinous compounds containing beeswax and partially digested exudates from plants leaves and buds. Its chemical composition varies widely depending on the bee species, geographic location, plant species, and weather conditions. Since ancient times, propolis has been used in many conditions and aliments for its healing properties. Propolis has well-known therapeutic actions including antioxidative, antimicrobial, anti-inflammatory, and anticancer properties. In recent years, extensive in vitro and in vivo studies have suggested that propolis possesses properties against several types of cancers. The present review highlights the recent progress made on the molecular targets and signaling pathways involved in the anticancer activities of propolis. Propolis exerts anticancer effects primarily by inhibiting cancer cell proliferation, inducing apoptosis through regulating various signaling pathways and arresting the tumor cell cycle, inducing autophagy, epigenetic modulations, and further inhibiting the invasion and metastasis of tumors. Propolis targets numerous signaling pathways associated with cancer therapy, including pathways mediated by p53, β-catenin, ERK1/2, MAPK, and NF-κB. Possible synergistic actions of a combination therapy of propolis with existing chemotherapies are also discussed in this review. Overall, propolis, by acting on diverse mechanisms simultaneously, can be considered to be a promising, multi-targeting, multi-pathways anticancer agent for the treatment of various types of cancers.